Assessing the competence of junior doctors to prescribe for children. Issue 4 (11th March 2011) - Isaac, R; Marcus, R; McLellan, N
Abstract : Objective: The National Services Framework for Children states that persons involved in handling medicines for children should be competent to do so. This report describes the development of a process to assess the competence of doctors to prescribe for children while proving educational support. Method: A literature search, national guidance, local medication incidents and pharmacists interventions were analysed to determine areas of poor prescribing practices in children. An assessment paper was designed using hospital prescribing documentation to include common scenarios and practices involved in prescribing for children. The assessment paper was piloted and a marking scheme was developed to evaluate both standards of prescribing content and drug calculations. In addition an automatic referral would be made if any prescription was likely to result in patient harm. In addition to the assessment paper the doctors are given a copy of the hospital prescribing standards and the use of the British National Formulary for Children (BNFC) is allowed and recommended. Following marking, where standards are not met the individual and their educational supervisor is contacted with a copy of the completed paper and a feedback form. The feedback form contains the possible remedial options, including discussion with tutor and tutorial with a pharmacist. Doctors meeting standards are offered copies of the completed paper to add to their e-portfolios. Results: The following areas of prescribing were targeted for testing on the assessment paper: documentation of allergies; drug dosing according to age in addition to weight or body surface area; selection of the correct dose for indication from the BNFC; selection and calculation of correct intravenous fluids for children; awareness of different strengths of liquid medications for children, including unlicensed medicines; drug calculations involving conversion of ml to mg and ratio strengths. From the pharmacist intervention record specific drugs had a higher trend of poor prescribing, namely paracetamol, co-amoxiclav and aciclovir. These were included in the questions. Return of papers is variable, 56% overall. Of the completed papers three quarters of the doctors achieved a good standard. 19.7% of the papers contained errors which had the potential to cause harm to a patient. These errors included selection of the incorrect strength or route of epinephrine for anaphylaxis, incorrect conversion from ml to mg. Selection of inappropriate intravenous fluids was a common error in doctors that had recently undertaken an adult rotation. Conclusion: While the prescribing assessment was introduced to reduce errors, it is becoming more important as an educational tool. It is also evolving to becoming a source of evidence for the doctors of their ability to prescribe in children. The areas of poor prescribing from the assessment mirror the literature but give the opportunity to target the areas for educational intervention for both undergraduate medical students and postgraduate doctors working in paediatrics.